2018
DOI: 10.1111/asj.13149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substituting kraft pulp with corn silage on dry matter intake, ruminal mat formation, rumen fermentation, and rumination activity in non‐lactating cows

Abstract: The present study examined the effects of substituting kraft pulp (KP) with corn silage (CS) on dry matter intake (DMI), ruminal mat and rumen fermentation characteristics, and rumination. Four non‐lactating, rumen‐cannulated Holstein cows were fed a CS diet comprising 36% grass silage (GS) and 64% CS or a KP diet comprising 36% GS, 57% KP, and 7% soybean meal. DMI was significantly lower in cows fed the KP diet than in those fed the CS diet (p < 0.05), whereas rumination time did not significantly differ betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…KP has a total digestible nutrient (TDN) value equivalent to rolled corn and a slow in situ digestion rate (Hada et al, 2016). Therefore, KP may be a suitable alternative to not only roughage (Izumi et al, 2019; Maeda, Kawasumi, et al, 2019) but also to concentrated feed (Kido et al, 2019; Kim et al, 2019; Maeda, Nishimura, et al, 2019; Nishimura et al, 2019). In addition, recent studies suggested that KP supplementation in concentrated feed for Holstein cattle could suppress the decline in ruminal pH (Nishimura et al, 2019), resulting in reduced ruminal lipopolysaccharide (LPS) activity (Kim et al, 2019; Nishimura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…KP has a total digestible nutrient (TDN) value equivalent to rolled corn and a slow in situ digestion rate (Hada et al, 2016). Therefore, KP may be a suitable alternative to not only roughage (Izumi et al, 2019; Maeda, Kawasumi, et al, 2019) but also to concentrated feed (Kido et al, 2019; Kim et al, 2019; Maeda, Nishimura, et al, 2019; Nishimura et al, 2019). In addition, recent studies suggested that KP supplementation in concentrated feed for Holstein cattle could suppress the decline in ruminal pH (Nishimura et al, 2019), resulting in reduced ruminal lipopolysaccharide (LPS) activity (Kim et al, 2019; Nishimura et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, this factor was not enough to cause physical limitations and reduce the DM intake for the diets supplemented with babassu cake, possibly due to the physical characteristics of the babassu cake (i.e., the small size of its particles). This resulted in the low effectiveness of the fiber in the rumen; it is likely that the potentially degradable fractions were quickly digested by the sheep after ingestion, thus preventing a filling effect (Izumi, Tamura, Fujii, Nakatsuji, & Morita, 2018). The characteristics of the babassu cake made the degradation process more efficient by ensuring sufficient contact surfaces for the colonization of microorganisms and reducing the retention capacity of these particles in the rumen (Kammers & Allen, 2011;Gomes et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Nishimura et al (2019) evaluaron la inclusión de pulpa de papel (12%) en la dieta de vacas lecheras, como remplazo del 50% del maíz de la ración y no encontraron diferencias significativas en el Consumo de Materia seca (CMS) respecto al tratamiento control. Maeda et al (2019) incluyeron 12% de pulpa de papel (Kraft) en dietas de novillos de engorde, sin evidenciar diferencias significativas en el CMS respecto al grupo control (concentrado y forraje), mientras queIzumi et al (2019), al remplazar el ensilaje de maíz con la inclusión de pulpa de papel (Kraft) hasta un 57% en dietas en vacas lecheras, encontró una reducción en el CMS, indicando que la inclusión de altos niveles de este tipo de materiales en la ración de los rumiantes, afecta el CMS.…”
unclassified